Diagnóstico das sanções administrativas aplicadas aos fornecedores de uma instituição pública de ensino - FERREIRA, Thassiana Bessa (2019)
The Administrative Process of Responsibility Determination - PAAR aims to determine the responsibility of the suppliers in a public educational institution, both in the selection phase and in the execution phase of the contract, applying, when necessary, administrative sanctions. The establishment of PAAR demonstrates the need to identify and intervene in recurring problems of Public Administration, aiming at greater efficiency and transparency of administrative processes. Based on these facts, this paper proposes to identify and measure possible failures of these suppliers in the selection process and in the execution of administrative contracts, thus allowing for more efficiency during the internal procedures and, consequently, the reduction of cases of establishment of PAAR. The present research was based on qualitatives studies, with descriptive focus, which allowed a general analysis of the problem studied. In addition, we used bibliographical and documentary research, as well as the case study. Finally, the data obtained were tabulated and later analyzed statistically. From the analysis, it was possible to extract the year of opening, installation and completion of the PAAR, its origin, type of object, bidding modalities, main reasons that caused these processes, penalties applied, penalties, PAAR duration and overview of the lawsuits and rescinded cases. The obtained results allowed to affirm that the "non delivery of the object" is the prevalent reason that causes the installation of PAAR in the Federal University of Triângulo Mineiro - UFTM and that there was a significant improvement in the internal procedures, including as far as the duration of the procedural instruction until its finalization. The main impacts of this motive were: the mobilization of public management to manage the PAAR, loss of the committed public budget, work stoppage and commitment of funding resources for space leasing, non-receipt of important goods and materials and commitment of the operation of outsourced cleaning and safety activities. All steps of the PAAR were analyzed, which made it possible to suggest improvement recommendations for management practice. This work will constitute the collection of the literature, supplying the shortage of works in this area of public management and will serve as a parameter for future improvements in the question of responsibility of suppliers in public educational institutions.